IDENTIFICATION OF SELF POSITION AND BASIC ATTITUDE OF COUNSELORS BY SEMAR TEXT (Study Analysis OF Hermeneutik Gadamerian) - Gumilang, Galang Surya (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
The purpose of this study are to know: (1) self-position of counselor which was adopted from the text of Semar, (2) The basic attitude which was adopting from the text of Semar, (3) The technic for communicating base attitude of counselor are using the metaphor in counseling. This research uses the Qualitative approach by Gadamerian hermeneutic method. Gadamerian hermeneutics is a kind of objective hermeneutic research (Objectivist hermeneutics). Gadamerian hermeneutics unifying thought is contained in a hermeneutic circle pattern. The circle consists of a pattern of up and down between the parts (part) and overall (whole) to understand the meaning of a text. The Data of research are including two texts such as what and who Semar is? (Mulyono, 1978) and Semar as spiritual world of Javanese (Sumukti, 2006), data of interview with Ki Manteb Sudarsono, Ki Purbo Asmoro, S.Kar., M.Hum and Dra. Sri Saptaningsih, MM and data watching the video of wayang. The result of research show that self-position of counselor which was adopted from the text of Semar are: (1) advicer, (2) motivator, (3) deterrent, (4) servant. The basic attitude which was adopting from the text of Semar are: (1) hospitable, (2) wise, (3) honest, (4) care. The technic for communicating basic attitude of counselor are using advice technique.Key Words: The position counselor, the basic attitude of counselor, Semar text.